Faktor Keberhasilan Implementasi Kebijakan Penyelenggaraan Haji Di Kota Bandung - Jaliludin Muslim (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
The service of organizing the pilgrimage is actually every year always strived to be better. The Government through the Indonesian Ministry of Religion in Bandung, should be able to implement the Implementation of Hajj Implementation Policy optimally and effectively, without ignoring the formal legal rules that have been established so far. This study aims to analyze the factors of success and failure of implementing the implementation of the pilgrimage policy in the city of Bandung. The approach used in this study is a qualitative approach, where researchers are directly involved in the study site through observation and participant observation. The type of data from this study are primary data and secondary data. Primary data in the form of information and data from interviews with interested parties and the main actors in the implementation of the pilgrimage in the city of Bandung. Secondary data sourced from articles, literature studies, documents and photos, statistical data, archives both from the government and the public as well as mass media publications. The results of this study indicate that in the process of implementing the implementation of the pilgrimage policy in the city of Bandung faces a number of challenges that are not easy so that several factors emerge that led to the success or failure of the implementation process. This study can be concluded that the implementation of the Hajj policy in the city of Bandung in 2016 has not been carried out properly, due to a paradoxical reality towards the ideal policy that has been determined.